PENGARUH SPIRITUALITAS TEMPAT KERJA DAN PEMBERDAYAAN KARYAWAN TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA (INTRINSIK) SEBAGAI VARIABEL INTERVENING - Putri, Rosalia Bina Pranata; Yuniawan, Ahyar (Diponegoro Journal of Management, 2016)
Employee performance is an important element in a company. The performance of good employees are able to make the company achieve its goals. When companies have employee performance is good then the company has a good ability to compete. Various things can be made to improve employee performance. As is the case in this study aimed to analyze whether the workplace spirituality and employee empowerment affect the performance of employees with work motivation (intrinsic) as an intervening variable.This research was conducted with a sample of 124 employees of the distribution of questionnaires Islamic Hospital Sultan Agung Semarang using disproportionate stratified random sampling technique with respondents consisting of staff, head of the section, and manager. The analytical method used is the analysis of Structural Equation Modeling (SEM).The results of SEM analysis showed that the workplace spirituality does not have a significant effect on work motivation (intrinsic) but significant positive effect on employee performance, employee empowerment has no significant effect on work motivation (intrinsic) and employee performance, and employee motivation (intrinsic) had no significant influence on employee performance.